Path of Blood: The Story of Al Qaeda's War on the House of Saud - Small, Thomas and Hacker, Jonathan (London Simon and Schuter, 2014)
Path of Bloodtells the gripping and horrifying true story of the underground army which Osama Bin Laden created in order to attack his number one target: his home country, Saudi Arabia. His aim was to conquer the land of the Two Holy Mosques, the land from where Islam had first originated and, from there, to re-establish a Muslim Empire that could take on the West and win. With the West unpopular with many Saudis at the time of the Iraq and Afghan wars, the Al Qaeda leadership lured impressionable recruits to the organisation with a mix of religious and political rhetoric as well as the promise of glory and heavenly riches. Many joined, and a murderous and highly visible campaign of kidnapping, shootings and bombings was launched across the country. And yet, a far cry from the image they promoted of themselves as single-minded guerrilla tacticians, authors Jonathan Small and Thomas Hacker's new insider evidence reveals the Al Qaeda infighting, the fooling around, and the training sessions which sometimes descended into farce. Yet the threat they posed was unquestionable. Ill-disciplined or not, these were men who killed with impunity, and who tried to acquire a nuclear bomb. Drawing on unprecedented access to Saudi government archives, interviews with top intelligence officials both in the Middle East and in the West, as well as with captured Al Qaeda militants, and with access to exclusive captured video footage from Al Qaeda cells, Path of Bloodtells the full story of the terrorist campaign and the desperate and determined attempt by Saudi Arabia's internal security services to put a stop to it.
Includes Illustrations, notes and Index.
Keywords: Terrorists -- Saudi Arabia